2019
DOI: 10.1177/2158244019825914
|View full text |Cite
|
Sign up to set email alerts
|

Patriarchy and Women Vulnerability to Adverse Climate Change in Nigeria

Abstract: The article explored the linkages between patriarchy and the high rate of women’s vulnerability to climate change. It examined how traditional beliefs, which underpin cultural division of roles between men and women, also increase the vulnerability of women to the adverse impacts of climate change. The article argued that the centralization of activities of women to occupations such as small-scale and rain-fed agriculture makes them more vulnerable to climate-related problems than the men. The article relied o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(36 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…The results of the survey showed a strong correlation between gender and adaptation level, with women more likely to have low levels of adaptation (Boko 2007). Further analysis showed that women and men in developing nations do not have equal access to climate change adaptation tools in agriculture, with men more likely to have higher access (Onwutuebe 2019). Other studies in various regions in Africa recorded similar results (MacGregor 2010; Ume 2018).…”
Section: Gender and Vulnerabilitymentioning
confidence: 58%
“…The results of the survey showed a strong correlation between gender and adaptation level, with women more likely to have low levels of adaptation (Boko 2007). Further analysis showed that women and men in developing nations do not have equal access to climate change adaptation tools in agriculture, with men more likely to have higher access (Onwutuebe 2019). Other studies in various regions in Africa recorded similar results (MacGregor 2010; Ume 2018).…”
Section: Gender and Vulnerabilitymentioning
confidence: 58%
“…The foundation of young peoples' attitudes and expectations in respect of their identity and role are created by these gendered norms. In the light of this, young men are reported to have a sense of entitlement towards their female partners and may resort to IBSA or other forms of electronic abuse if they feel their exclusive right over their women is being threatened (Edinyang & Angiating, 2018;Onwutuebe, 2019). For example, a popular Lagos-Nigeria based pastor, Chris Omatsola, was reported to have released online a sex videotape with his former lover, which they had both recorded consensually (The Punch, 2019).…”
Section: Theoretical Background: Feminism Male Support Theory and Nimentioning
confidence: 99%
“…The authors’ findings also included the dominance of male roles in this comment by a 24-year-old male, “ because they [men] are perceived as the best in all aspect [s] especially on specific issues [e.g. inheritance, leadership, physical work, etc].” Commenting on a feminist theory, Onwutuebe (2019, p. 3) despises patriarchal institutions as an establishment of power imbalance against women, and continuous gender disparity in Africa. In the view of the authors, gender equality movements should adopt anthropological lenses in exploring complementary roles of the sexes in adult education curriculum.…”
Section: Resultsmentioning
confidence: 96%